2009
DOI: 10.1029/2008jd011333
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term production and synoptic influences on atmospheric 7Be concentrations

Abstract: Variations of the cosmogenic radionuclide 7Be in the global atmosphere are driven by cooperation of processes of its production, air transports, and removal. We use a combination of the Goddard Institute for Space Studies ModelE and the OuluCRAC:7Be production model to simulate the variations in the 7Be concentration in the atmosphere for the period from 1 January to 28 February 2005. This period features significant synoptic variability at multiple monitoring stations around the globe and spans an extreme sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…A simulation performed by combining a detailed 10 Be-production model with an air-dynamics model can result in an absolute model relating production and deposition of the radionuclide. The validity and usefulness of this approach has been demonstrated by Usoskin et al (2009a), who directly modeled production (using the CRAC model-Usoskin and Kovaltsov 2008b) and transport (using the GISS ModelE- Koch et al 2006) of a short-living beryllium isotope 7 Be and showed that such a combined model is able to correctly reproduce both the absolute level and temporal variations of the 7 Be concentration measured in near ground air around the globe. Keeping in mind the similarity between production and transport of the two beryllium isotopes, 7 Be and 10 Be, this serves as support for the advanced modelling of 10 Be transport.…”
Section: Atmospheric Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…A simulation performed by combining a detailed 10 Be-production model with an air-dynamics model can result in an absolute model relating production and deposition of the radionuclide. The validity and usefulness of this approach has been demonstrated by Usoskin et al (2009a), who directly modeled production (using the CRAC model-Usoskin and Kovaltsov 2008b) and transport (using the GISS ModelE- Koch et al 2006) of a short-living beryllium isotope 7 Be and showed that such a combined model is able to correctly reproduce both the absolute level and temporal variations of the 7 Be concentration measured in near ground air around the globe. Keeping in mind the similarity between production and transport of the two beryllium isotopes, 7 Be and 10 Be, this serves as support for the advanced modelling of 10 Be transport.…”
Section: Atmospheric Transportmentioning
confidence: 99%
“…Comparison of model computations with direct beryllium production experiments (Usoskin and Kovaltsov 2008b;Kovaltsov and Usoskin 2010), and also the results of modelling of the short-living 7 Be isotope (Usoskin et al 2009a) suggest that some numerical models (Masarik and Beer 1999;Webber and Higbie 2003;Webber et al 2007) tend to underestimate the production.…”
Section: Productionmentioning
confidence: 99%
“…There is discrepancy of a factor of 1.5 between different production models of 10 Be production that needs to be resolved. Comparison of model computations with direct beryllium production experiments Kovaltsov and Usoskin, 2010), and also the results of modelling of the short-living 7 Be isotope (Usoskin et al, 2009a) suggest that some numerical models (Masarik and Beer, 1999;Webber and Higbie, 2003;Webber et al, 2007) tend to underestimate the production.…”
Section: Productionmentioning
confidence: 99%
“…Although these global 3-D models have shown remarkable skills in simulating the tropospheric beryllium cycle (e.g. Usoskin et al, 2009), they do not include yet adequate descriptions of stratospheric aerosol microphysical processes for the study of the stratospheric beryllium cycle. We note that the SOCOL 3-D chemistryÁ climate model has been very recently coupled to the detailed aerosol microphysics of the 2-D AER model (Sheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%